ANALISIS KINERJA JARINGAN LAN MENGGUNAKAN METODE QUALITY OF SERVICE (QOS) (Studi Kasus : PT. Transportasi Gas Indonesia Di Jambi) - sudrajat sudrajat; Mega Wahyu Ramadhani (Fakultas Teknik Unkris Jakarta, 2022)
PT. Transportation Gas Indonesia is a company engaged in the oil and gas, specialy as a natural gas distributor. In operasionality has some fairly complex gas field. In some of the gas field using a network of Wireless Local Area Network (WLAN). To find out how much the performance (performance) PT.Transportasi Gas network in Indonesia, it should be an examination and analysis of network performance with base on quality of service (QoS). QoS is the ability to assure delivery of network data flow or a set of criteria that determine the level of satisfaction capability of using a jaringan.Parameter QoS is composed of bandwidth, delay and packet loss.